2021
DOI: 10.1002/ehf2.13604
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and prognostic implications of capillary density in patients with cardiac light chain amyloidosis

Abstract: Aims Cardiac involvement is crucial factor determining outcomes of light chain (AL) amyloidosis. This study evaluated whether capillary density (CD) quantified from endomyocardial biopsy is associated with structural and functional parameters of amyloid heart. Also, we investigated whether capillary density improves the prognostic value of the current staging system in AL amyloidosis patients with cardiac involvement. Methods and results A total of 67 patients with biopsy‐proven AL cardiac amyloidosis were pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…In symptomatic patients with AL or transthyretin amyloidosis, myocyte blood flow became lower than in hypertensive patients exhibiting LV hypertrophy 57) . Recently, Kim et al showed direct evidence of reduced capillary density in AL amyloidosis patients 58) . They analyzed cardiac biopsy samples and showed capillary density had a negative correlation with NT-proBNP level, amyloid load, LV diastolic, and systolic function 58) .…”
Section: -6 Amyloidosismentioning
confidence: 99%
See 2 more Smart Citations
“…In symptomatic patients with AL or transthyretin amyloidosis, myocyte blood flow became lower than in hypertensive patients exhibiting LV hypertrophy 57) . Recently, Kim et al showed direct evidence of reduced capillary density in AL amyloidosis patients 58) . They analyzed cardiac biopsy samples and showed capillary density had a negative correlation with NT-proBNP level, amyloid load, LV diastolic, and systolic function 58) .…”
Section: -6 Amyloidosismentioning
confidence: 99%
“…Recently, Kim et al showed direct evidence of reduced capillary density in AL amyloidosis patients 58) . They analyzed cardiac biopsy samples and showed capillary density had a negative correlation with NT-proBNP level, amyloid load, LV diastolic, and systolic function 58) . In this paper, the patients exhibiting capillary density of >220/mm 2 were shown to have a better prognosis than those exhibiting <220/mm 2, 58) .…”
Section: -6 Amyloidosismentioning
confidence: 99%
See 1 more Smart Citation
“…The investigators of this study also quantified capillary density on the EMB samples as the number of capillaries, which were counted after they were stained with a specific antibody against endothelium (CD31), divided by area (mm 2 ). The authors reported that lower capillary density correlated with amyloid load and predicted mortality among 67 patients with biopsy-proven AL cardiac amyloidosis ( 12 ). When added to the 2012 Mayo staging system, capillary density led to better discrimination and reclassification ability compared to the 2012 Mayo staging system alone ( 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…In some recent reports, the prognostic value of these systems has been augmented with echo-derived strain patterns, such as left ventricular (LV) global longitudinal strain (GLS) and the apical to basal longitudinal strain gradient ( 11 ). Furthermore, the capillary density within the myocardium on histopathology has also been shown to improve the prognostic value of the 2012 Mayo staging system ( 12 ).…”
Section: Introductionmentioning
confidence: 99%